Forecasting the macroeconomy with current financial market information: Europe and the United States - Juha Junttila (Bank of Finland, 2002)
Using recently developed modelling methodology of Economic Tracking Portfolios (ETP), we find that it is possible to forecast future values of inflation and changes in industrial production in the United States and at least three core euro countries - Italy, France and Germany - utilising only current and past financial market information.The longer the forecasting horizon, the better the forecasts based solely on financial market information compared to results from other methods.Of the analysed countries, the overall forecasting performance of the tracking portfolios is the best for the United States, and the method employed here clearly outperforms the forecasting performance of a more traditional VAR approach.
URN:NBN:fi:bof-20140807322
Keywords: 330; financial markets; forecasting; macroeconomy; euro area; USA